Relationship Between Periodontal Disease (Periodontitis) and Major Vascular Events. A Case- Control Study. Enperiva Studio - Pablo A. Olavegogeascoechea; José A. Allevato; Facundo N. Olavegogeascoechea; Pablo Contreras; Gabriela Valenzuela; Pedro L. Urdiales (European Scientific Journal, ESJ, 2017)
Introduction: Periodontal and vascular disease share not only risk factors such as smoking and diabetes, but also a complex and multifactorial process of chronic inflammation. Materials and Methods: We carried out “case-control study”. The cases were included in a non-randomized manner and they have to had a major vascular event at entry. Results: The proportion of patients with periodontitis was significantly higher in cases than in controls (p = 0.02). The presence of gingivitis was almost the same in both groups (p = 0.99). Conclusions: The present study demonstrated that not only periodontal disease is strongly associated with major vascular events but also that it was independent of traditional risk factors for vascular disease.